1956
DOI: 10.1136/bmj.1.4966.555
|View full text |Cite
|
Sign up to set email alerts
|

Hazards of the Menstrual Cycle

Abstract: PREVENTION OF BEDSORES BRITISH 55L MEDICAL JOURNAL Observations over a period of six months show that it is at least as effective as the usual method. The saving in nursing time and labour justifies its continued use. The cost of treatment is low. Further trials are in progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1959
1959
2012
2012

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(17 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…2 gives the time of admissions of 36 attempted suicides and shows a relative incidence rate during menstruation of 2.75 or 39%. This figure of 39% of attempted suicides during menstruation compares with the figure of 36% reported by Heller in 1900, 22%by Ollerdorf in 1905, and 33% by Slavik in 1910 (quoted by Gregory, 1957, and supports the findings of MacKinnon and MacKinnon (1956) that successful suicides seem commoner during the luteal phase. Figs.…”
supporting
confidence: 83%
“…2 gives the time of admissions of 36 attempted suicides and shows a relative incidence rate during menstruation of 2.75 or 39%. This figure of 39% of attempted suicides during menstruation compares with the figure of 36% reported by Heller in 1900, 22%by Ollerdorf in 1905, and 33% by Slavik in 1910 (quoted by Gregory, 1957, and supports the findings of MacKinnon and MacKinnon (1956) that successful suicides seem commoner during the luteal phase. Figs.…”
supporting
confidence: 83%
“…MacKinnon and MacKinnon (1956) reported that, in a series of 47 post-mortem examinations on women of reproductive age, death was found to have occurred in 45 cases during the luteal phase of the menstrual cycle. In the last two years 55 post-mortem examinations have been added to the series, and in these also the great majority of deaths occurred during the luteum.…”
Section: Discussionmentioning
confidence: 99%
“…If, however, the necessary comparison is made between the age distributions of my practice and the depressed patients ( Fig. 1) MacKinnon, 1956), as are also psychiatric illnesses (Dalton, 1959), including depression and anxiety (Coppen, 1965 (Taylor and Chave, 1964;Hare and Shaw, 1965). There was no evidence that caring for a large family predisposed a mother to a depressive illness.…”
Section: Characteristics Of Patients Studiedmentioning
confidence: 99%